Paying to avoid the spotlight - Bao Te; John Duffy; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2024)
In the digital age, privacy in economic activities is increasingly threatened. In considering policies to address this threat, it is useful to consider what value, if any, that people attach to privacy in economic activities. We study this question by eliciting individuals' willingness to pay (WTP) to avoid detection in an economic experiment involving a coin-flipping task. We collect data from Japan, China, and the U.S.A. to examine whether there are cross-country differences. Our findings reveal that people's WTP to "avoid the spotlight" is positive and economically sizable across all three countries and is the largest in Japan.
Keywords: C91; D83; D91; 330; Privacy; Monitoring; Surveillance; Willingness to Pay; Dishonesty; Lying; Social Image Concerns